Dynamics of Economic Growth on The Island of Sumatra Before and After The Covid-19 Pandemic: Panel Data Analysis - Abizar Al Ghiffari, Hadraji Mufti; Qina Khaitsa; Pundari Zuhayka; Saffa Namira (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2025)
This study aims to analyze the influence of inflation, investment, and government spending on economic growth on the island of Sumatra during the period 2017–2023. Using the panel data regression method, this study combines interprovincial and intertemporal data variations to obtain a more comprehensive picture of economic dynamics before and after the COVID-19 pandemic. The results of the analysis show that simultaneously the three variables have a significant influence on regional economic growth. Partially, investment has proven to have a positive and significant influence so that it is the main factor driving economic growth, especially in the post-pandemic recovery phase. Inflation also shows a positive and significant influence, which indicates that price stability is able to support regional economic activity. Meanwhile, government spending has a positive but insignificant effect, so the effectiveness of regional fiscal allocation still needs to be improved in order to be able to have a stronger economic impact. Overall, these findings confirm that creating a conducive investment climate and improving the quality of government spending are key to encouraging sustainable economic growth on the island of Sumatra.